Same Species, Different Breed: The Conditional Effect of Legislator Activities in Parliament on Re-Selection in a Mixed-Member Electoral System. Issue 1 (31st January 2018) - Papp, Zsófia
Abstract: The article investigates whether or not the amount of work legislators carry out in parliament affects their chances of re-selection in a mixed-member electoral system. A unique dataset collecting Hungarian Members of Parliaments' (MPs) publicly available electoral, socio-demographic and parliamentary activity data between 1998 and 2010 is analysed. The study concludes that activity in parliament positively influences re-selection chances when selectors decide on party list nominations. Additionally, MPs whose parties do not count on as future Single Member District (SMD) candidates benefit from parliamentary work to a greater extent than prospective SMD candidates. At the same time, extra work in parliament does not bring MPs closer to SMD nominations. Results confirm that selectors evaluate MPs along how well they carry out the tasks dedicated to their groups.